Enhanced Supervised Fuzzy Clustering For Pattern Classification - Lim , Kian Ming (2010)
Classification is the problem of discovering homogenous groups of data points in a given data set, which is called a cluster. In this thesis, the term classification and clustering are used interchangeably. In real application, the performance of classification method has to meet three properties, namely deterministic decision, missing data due to sensor failure and high dimensionality of data.